2006
DOI: 10.1021/bi0617355
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effects of Potassium Ion Binding on Wild-Type and L358P Cytochrome P450cam

Abstract: The camphor monoxygenase cytochrome P450 cam (CYP101) requires potassium ion (K + ) to drive formation of the characteristic high-spin state of the heme Fe +3 upon substrate binding. Amide 1 H, 15 N correlations in perdeuterated [U-15 N] CYP101 were monitored as a function of K + concentration by 2D-TROSY-HSQC in both camphor-bound oxidized (CYP-S) and camphor-and CO-bound reduced CYP101 (CYP-S-CO). In both forms, K + -induced spectral perturbations are detected in the vicinity of the K + binding site proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Although many metal-containing co-factors (e.g., heme, chlorophyll, cobalamin) are pre-formed when finally bound to their protein partners, this still requires that the co-factors themselves be properly synthesized with the correct metal. Alkali metal and alkaline earth ions are sometimes bound via amide carbonyl oxygens (as in selective ion channels 110 or when stabilizing local structural motifs 111 ). In these cases, the protein backbone conformations appear to be pre-arranged to selectively bind cations of the appropriate size and charge.…”
Section: Perspectivementioning
confidence: 99%
“…Although many metal-containing co-factors (e.g., heme, chlorophyll, cobalamin) are pre-formed when finally bound to their protein partners, this still requires that the co-factors themselves be properly synthesized with the correct metal. Alkali metal and alkaline earth ions are sometimes bound via amide carbonyl oxygens (as in selective ion channels 110 or when stabilizing local structural motifs 111 ). In these cases, the protein backbone conformations appear to be pre-arranged to selectively bind cations of the appropriate size and charge.…”
Section: Perspectivementioning
confidence: 99%
“…Binding of potassium was proposed to stabilize an otherwise unfavourable B 0 helix in the enzyme leading to a conformational change resulting in the removal of water from the active site and an increase in the affinity for the substrate [8,[11][12][13]. A recent NMR study demonstrated widespread change in the backbone polypeptide conformation of the enzyme as a result of potassium binding to the enzyme in presence of camphor [14]. Substitution of the potassium ion by monovalent cations were shown to drastically decrease the camphor binding affinity of P450cam [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we conclude that upon binding of Pdx, oxidized P450cam remains in the closed state in solution at 25°C. All studies on the structure of P450cam in the presence of Pdx used samples containing between 50 and 200 mM KCl, and potassium ions have been implicated in stabilizing the closed form of P450cam when camphor is bound (41). Therefore, in this study, the Leu-labeled samples used to determine the state of P450cam in the presence of Pdx (Table S1, (42).…”
mentioning
confidence: 99%